Discontinuing routine histopathological analysis after adult tonsillectomy for benign indication. (3rd February 2015) - Chow, Winsion; Rotenberg, Brian W.
<x xml:space="preserve">Abstract</x> Objective This study examines the rate of occult malignancy in routine histopathological analysis of tonsillectomy specimens from benign surgical cases in adults. Study Design Retrospective data review. Methods 181 consecutive charts of tonsillectomies performed for benign indications between March 2007 and March 2014 were reviewed. Data on age, indications for surgery, preoperative and intraoperative clinical findings, and final pathology results were collected. A literature review of studies examining the rate of occult malignancy in tonsillectomy specimens was also performed, and the combined data was pooled. The financial impact of routine tonsil pathological analysis was determined. Results In 181 patients, there was one case of occult malignancy. After study inclusion and exclusion criteria were met, a review of the literature yielded 3, 724 pooled tonsillectomy cases, with no case of unsuspected occult malignancy reported in the literature. The number needed to screen combining our series with the reported literature was 3, 904. The financial impact of routine histopathological analysis at our institution was determined to be CAD $3308 per year. Conclusion Routine pathological analysis of tonsil specimens recovered from surgery performed for benign indications, in the absence of any suspicion preoperatively for malignancy, is not supported by current evidence and is not financially sound. Modern evidence does not support the need for even gross specimen analysis in these cases. Level of Evidence 4. Laryngoscope, 125:1595–1599, 2015